Digital Transformation of Student Financial Management Through E-Money: A Case Study at SMAIQu Al-Bahjah Cirebon - Novitasari, Kartika; Sulfiani, Sulfiani; Sarie, Dwi Mutiara; Susilawati, Susilawati; Fitria, Faning Maulida (Sunan Kalijaga International Journal on Islamic Educational Research, 2025)
This study investigates the transformation of student financial management through the implementation of the Mumtas e-money system at SMAIQu Al-Bahjah Cirebon, a pesantren-based secondary school. The study aims to examine how the transition from physical vouchers to e-money influences institutional governance, financial supervision mechanisms, and students’ financial behavior. A qualitative case study approach was employed, drawing on in-depth interviews, non-participant observations, and document analysis involving key institutional stakeholders and parents. The findings indicate that e-money implementation enhances efficiency, transparency, and parental involvement, while supporting principles of accountable financial governance. Nevertheless, the supervision system remains partially manual due to infrastructure constraints, limited system integration, and the absence of structured financial literacy education for students. The study highlights the potential of e-money not only as a transactional instrument but also as a governance and educational tool within Islamic boarding school contexts. The research is limited by its single-case design, which restricts broader generalization. Future studies are recommended to adopt comparative and mixed-method approaches and to explore the long-term impacts of integrating e-money systems with formal financial literacy programs.